Radicalization: why some people choose the path of violence - Khosrokhavar, Farhad (The New Press, 2017)
Introduction: the notion of radicalization -- The history of radicalization -- Islamist radicalization in the Muslim world -- The Jihadist intelligentsia and its globalization -- The Web -- Financing radicalization -- Sites of radicalization -- The ambiguous role of frustration in radicalization -- The European model of radicalization -- The new radicalism on the march -- Radicalization versus deradicalization -- Conclusion